Moving with the Times: The Health Science Alliance (HSA) Biobank, Pathway to Sustainability. Issue 16 (March 2021) - Quinn, Carmel M; Porwal, Mamta; Meagher, Nicola S; Hettiaratchi, Anusha; Power, Carl; Jonnaggadala, Jitendra; McCullough, Sue; Macmillan, Stephanie; Tang, Katrina; Liauw, Winston; Goldstein, David; Zeps, Nikolajs; et al.
Human biobanks are recognised as vital components of translational research infrastructure. With the growth in personalised and precision medicine, and the associated expansion of biomarkers and novel therapeutics under development, it is critical that researchers can access a strong collection of patient biospecimens, annotated with clinical data. Biobanks globally are undertaking transformation of their operating models in response to changing research needs; transition from a 'classic' model representing a largely retrospective collection of pre-defined specimens to a more targeted, prospective collection model, although there remains a research need for both models to co-exist. Here we introduce the Health Science Alliance (HSA) Biobank, established in 2012 as a classic biobank, now transitioning to a hybrid operational model. Some of the past and current challenges encountered are discussed including clinical annotation, specimen utilisation and biobank sustainability, along with the measures the HSA Biobank is taking to address these challenges. We describe new directions being explored, going beyond traditional specimen collection into areas involving bioimages, microbiota and live cell culture. The HSA Biobank is working in collaboration with clinicians, pathologists and researchers, piloting a sustainable, robust platform with the potential to integrate future needs.